(untitled) (Journal of Bangladesh Academy of Sciences, 2014)
This study on turmeric was conducted at Sher-e-Bangla Agricultural University, Dhaka during the period from April 2010 to March 2011. Five different fertilizer combinations were used in this experiment. Number of tiller per clump, weight of mother rhizome per plant, weight of primary and secondary finger per plant were significantly highest from F2 and lowest from F0. Highest turmeric yield per hectare (11.6 t/ha) was obtained from F2 and the lowest (5.7 t/ha) was observed from F0. DOI: http://dx.doi.org/10.3329/jbas.v37i2.17559 Journal of Bangladesh Academy of Sciences, Vol. 37, No. 2, 189-193, 2013